Learning Model of Volcanic Eruption For Inculcating Attitude ff Response To Merapi Eruption In Elementary School Students In Boyolali district - Mukhlis Mustofa; Dewi Liesnoor Setyowati; Juhadi Juhadi; Suwito Eko Pramono (Universitas Negeri Semarang, 2021)
Natural disasters in Indonesia have the potential to cause sustainable systemic impacts if they are not addressed proportionally. Boyolali Regency as one of the regencies in Central Java Province has the potential for volcanic eruptions to occur in the Merapi slope area. The stronger mythology of the people who inhabit Merapi Lerang, compared to the eruption pattern that occurred in the Merapi area, is an interesting phenomenon. The planting of disaster education based on the Merapi eruption is needed in planting awareness from an early age in the form of disaster education. The formulation of this research problem is identified in five research questions, namely: How is the relationship between the role of local wisdom in the Merapi eruption area as a disaster education landscape to the development of education? How is the learning model that can be developed in the Merapi disaster-prone area in Boyolali district? How is the educational learning model in the context of developing the Merapi eruption response area as part of Indonesia? How to fulfill the educative rights of students in social studies learning as the embodiment of good citizens? This study uses a phenomenological qualitative approach, has an actual setting, researchers are the key instruments, the data are descriptive, emphasizes the process, sustainable disaster education is very important considering the complexity of regions in Indonesia that have various disaster potentials.